2013
DOI: 10.1371/journal.pone.0063002
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and In Vivo Scoring of Murine Experimental Autoimmune Uveoretinitis Using Optical Coherence Tomography

Abstract: Despite advances in clinical imaging and grading our understanding of retinal immune responses and their morphological correlates in experimental autoimmune uveoretinitis (EAU), has been hindered by the requirement for post-mortem histology. To date, monitoring changes occurring during EAU disease progression and evaluating the effect of therapeutic intervention in real time has not been possible. We wanted to establish whether optical coherence tomography (OCT) could detect intraretinal changes during inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 28 publications
(36 reference statements)
3
47
0
Order By: Relevance
“…They reported that in the rat EAU model, severe anterior inflammation develops during the active phase, which impedes the acquisition of precise OCT images of individual retinal layers. Recently, the use of SD-OCT to evaluate mouse EAU has been reported by Chen et al 21 and Chu et al 22 These two investigations, together with the present study, establish that the wide range of retinal pathology detected by OCT matches the findings of histological sections and fundus imaging. Chen et al 21 examined the efficacy of SD-OCT in evaluating retinal pathology of EAU in B10RIII mice that differs in severity and time course to the EAU model of B6 mice.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…They reported that in the rat EAU model, severe anterior inflammation develops during the active phase, which impedes the acquisition of precise OCT images of individual retinal layers. Recently, the use of SD-OCT to evaluate mouse EAU has been reported by Chen et al 21 and Chu et al 22 These two investigations, together with the present study, establish that the wide range of retinal pathology detected by OCT matches the findings of histological sections and fundus imaging. Chen et al 21 examined the efficacy of SD-OCT in evaluating retinal pathology of EAU in B10RIII mice that differs in severity and time course to the EAU model of B6 mice.…”
Section: Discussionsupporting
confidence: 83%
“…Chen et al 21 examined the efficacy of SD-OCT in evaluating retinal pathology of EAU in B10RIII mice that differs in severity and time course to the EAU model of B6 mice. However, Chu et al 22 demonstrated the utility of SD-OCT to investigate retinal vasculitis and leukocyte infiltration into the retina during EAU developed in C57BL/6 mice, but changes in the retinal outer layers including granuloma formation was not shown. Furthermore, to distinguish our study from the paper by Chu et al , we have indicated the correlation between OCT grades of EAU developed in B6 mice based on the criteria we have established and conventional clinical and histopathological grades in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…35 The animal models, such as experimental autoimmune uveoretinitis (EAU), support a role for autoimmunity with clinical-pathological features bearing remarkable similarity to man. 7,8,36,37 The currently held notion is that of a CD4 + T helper cell-driven process and supported in man by the association of sympathetic ophthalmia and Vogt-Koyanagi-Harada disease with specific HLA class II alleles as well as the identification of ocular antigen-responsive T cells in both the peripheral blood and eyes of patients. [38][39][40] When T cells are activated, they assume different functional phenotypes directed through canonical transcription factors 41,42 and characterised by the secretion of signature cytokines.…”
Section: Understanding Uveitismentioning
confidence: 99%
“…In experimental autoimmune uveoretinitis, the vitreous opacities detected by OCT corresponded to CD45+ cells that had infiltrated into the vitreous and were identified in histological sections [15] . Other groups have shown that similar foci of a size consistent with that expected from inflammatory cells were seen in eyes with posterior-segment inflammatory disease, such as ocular toxoplasmosis, during the active phases [10,16] .…”
Section: Discussionmentioning
confidence: 99%
“…Studies on an animal model of uveitis and on human eyes with uveitis concluded that the vitreal opacities seen in the OCT images, the same as the hyperreflective foci in the SD-OCT images, were most likely inflammatory cells [14,15] . In experimental autoimmune uveoretinitis, the vitreous opacities detected by OCT corresponded to CD45+ cells that had infiltrated into the vitreous and were identified in histological sections [15] .…”
Section: Discussionmentioning
confidence: 99%